Efficacy and safety of berberine for premature ventricular contractions: a meta-analysis and systematic review of randomized controlled trials - Meng Qiao; Chao Lei; Chaoren Tan; Cuncun Lu; Zijia Chen; Qiang Zhang; Zhifei Wang (Taylor & Francis Group, 2023)
AbstractContext Berberine is a potential drug that can effectively treat cardiovascular diseases, including premature ventricular contractions (PVCs).Objective This study was conducted to assess the efficacy and safety of berberine for PVCs.Methods The literature was searched using PubMed, Cochrane Library, Embase, China National Knowledge Infrastructure (CNKI), China Science and Technology Journal Database (VIP), Wanfang, and Chinese Biomedical Literature Database (CBM) for randomized controlled trials (RCTs) from inception to October 1, 2022. The risk of bias was assessed using the Revised Cochrane risk-of-bias tool for randomized trials, and the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) system was adopted to assess the quality of evidence.Results Ten RCTs with 896 participants were included in the meta-analysis. The results showed that compared to antiarrhythmic drugs (AD), berberine (BE) combined with AD had a higher effective rate (RR = 1.26; 95% CI:1.12, 1.42; p = 0.0001) with no significant incidence of adverse reactions (RR = 0.93; 95% CI:0.33, 2.57; p = 0.88), and BE alone had no significant difference in effective rate (RR = 0.91; 95% CI:0.77, 1.07; p = 0.23), and a lower incidence of adverse reactions (RR = 0.38; 95% CI:0.15, 0.97; p = 0.04) and recurrence rate (RR = 0.40; 95% CI:0.18, 0.88; p = 0.02).Conclusions The results suggest that BE is an effective and safe adjunctive method for PVCs. In addition, BE is recommended for patients with PVCs who had severe adverse reactions after administrating AD as an alternative therapy.